Pengaruh Simulasi PHET terhadap Literasi Sains Peserta Didik Kelas IX UPT SPF SMP Negeri 55 Makassar - Nadhia Nadhia; Ramlawati Ramlawati; Arie Arma Arsyad (Celebes Science Education, 2025)
This research aims to find out (1) How high is the level of scientific literacy of students who are taught using PhET simulations in static electricity class IX UPT SPF SMP Negeri 55 Makassar (2) How high is the level of scientific literacy of students who are taught using practical videos in static electricity material for class IX UPT SPF SMP Negeri 55 Makassar (3) Is there an influence of PhET simulation on students' scientific literacy in static electricity material for class IX UPT SPF SMP Negeri 55 Makassar. This type of research is Quasi Experimental Design research and Nonequivalent Control Group Design research design. The population of this study were all class IX students at UPT SPF SMP Negeri 55 Makassar. This sample was selected using Purposive Sampling Technique and obtained class IX.1 15 students as the experimental class and IX.2 15 students as the control class. The research instrument is scientific literacy test questions. Data were analyzed using descriptive and inferential statistics. The research results concluded: (1) The level of scientific literacy of class IX UPT SPF SMP Negeri 55 Makassar students who were taught using the PhET simulation was in the high category with an average score of 15.60. (2) The level of scientific literacy of class IX UPT SPF SMP Negeri 55 Makassar students who are taught using practical videos is in the low category with an average score of 7.53. (3) There is an influence of the PhET simulation on the scientific literacy of class IX UPT SPF SMP Negeri 55 Makassar students on static electricity material.